Descriptions of the second stage of music teachers' careers. (December 2016) - Conway, Colleen; Eros, John
The purpose of this study was to describe experiences of 12 second-stage music teachers as several themes emerged from a secondary analysis of previously collected written survey and interview data. Participants were previously involved in studies in which they were asked to reflect on their beginning teaching experiences and discuss their music teaching careers in the last 10 years (Conway, 2012a, 2012b). Data from the previous studies were then used in a secondary analysis in which we examined the data through the lens of "career cycle" and "second stage" theory. Experiences in the second stage included: (a) feeling settled; (b) assuming leadership; (c) uncertainty; and (d) seeking new challenges. These are discussed in relation to past research and suggestions for future research are provided.